Analisis Semiotik Ferdinand de Saussure Terhadap Nilai-Nilai Da’wah Pada Film Nussa dan Rara - Rizal Dj. Kasim; Zainuddin Soga; Alivia Heratika Mamonto (KOMUNIDA : Media Komunikasi dan Dakwah, 2022)
ABSTRACT This research to understand the overall view, understand the signifier and signified of da’wah value and the synopsis of da’wah message of Nussa and rara animated film. Research used qualitative method by semiotics analysis dialog, pieces of image, sound and tones included in Nussa and rara animated film. The result of this research is: first these films are under the house production of The Little Giantz, with youtube account under the name Nussa Official, the main concept of making this film is making Islamic thing concept. Secondly in the episode “good is easy” of Nussa and Rara, the research found three scene that implied culture and morals which the scene is explaining about speaking good and polite, a scene about only pray for good, and the scene about struggling and managing. And thirdly the character in the episode “good is easy” Umma, Nussa, Rara, and Anta. The episode duration is 06:52. The episode presents a good example of culture and morals. The implication of this research is parent, academics and educator, viewer, and the society, which expected to be an example and alternative form of studies helpin to shape the Islamic generation to have high sense of culture and morals in everyday life. Keywords : Islamic Values; Nussa and Rara; Semiotic Ferdinand de Saussure.